Teknologi Tepat Guna UMKM Kelompok Perikanan Kecamatan Kota Besi Kabupaten Kotawaringin Timur - Almardani Almardani; Slamet Riyadi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Appropriate technology is technology that is in accordance with the conditions in which technology is used and applied both from a social, economic and cultural perspective, so that users can easily participate and can fulfill their needs effectively and efficiently. Kota Besi Subdistrict Public Transport, has excellent products. As for some products from SMEs in Kota Besi Subdistrict, among others, catfish, catfish and others. In running its business, Kota Besi Subdistrict MSMEs in collaboration with local Fish Farming have several obstacles including the slow marketing of MSME products due to a lack of promotional media and limited marketing areas and the Kota Besi District UMKM products themselves are not well known by the community, causing products to sell slowly, Therefore, to overcome the above problems by creating an internet site, the manager can arrange up to date promotions according to the types of products and prices on the market and can adjust to consumer needs. By utilizing information technology, it can make it easier for consumers to choose and order products by looking directly at the type, weight and price of the product according to their needs without having to come to the location